2014
DOI: 10.1371/journal.pone.0096711
|View full text |Cite
|
Sign up to set email alerts
|

The Deficiency of Tumor Suppressor Prep1 Accelerates the Onset of Meis1- Hoxa9 Leukemogenesis

Abstract: Prep1 and Meis1 ortholog TALE transcription factors have opposing roles in tumorigenesis: Meis1 serves as an oncogene, Prep1 as a tumor suppressor. We now report that, Meis1 overexpression in primary Prep1-deficient (Prep1i/i) embryonic hematopoietic cells increases self-renewal potential of cells in vitro but not in vivo, whereas leukemia is instead obtained when Meis1 is combined with another oncogene, HoxA9. Prep1i/i Meis1-HoxA9-generated leukemic cells are less differentiated and grow more aggressively aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…Recent studies by the Blasi group support and complement our findings [43, 44]. They found that Prep1 (Pknox1) competes with Meis1 for binding to Pbx1, and Prep1 depletion enabled Meis1 to transform MEFs [43].…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…Recent studies by the Blasi group support and complement our findings [43, 44]. They found that Prep1 (Pknox1) competes with Meis1 for binding to Pbx1, and Prep1 depletion enabled Meis1 to transform MEFs [43].…”
Section: Resultssupporting
confidence: 82%
“…They found that Prep1 (Pknox1) competes with Meis1 for binding to Pbx1, and Prep1 depletion enabled Meis1 to transform MEFs [43]. Additionally, depletion of Prep1 accelerated the onset of Meis1-Hoxa9 -mediated leukemogenesis in a murine model [44]. They hypothesized that increasing PREP1 levels may be an important area for future therapeutic development [43].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The oncogenic properties of MEIS1 are antagonistically regulated by PREP1, another TALE family protein, through direct competition for binding sites (68). PREP1 also competitively heterodimerizes and sequesters PBX proteins, thereby decreasing stability of MEIS1 and preventing the MEIS1-DDX3x/DDX5 interactions that are required for tumorigenesis (69, 70). Furthermore, in vivo leukemogenesis studies with HOXA9/MEIS1 in PREP1-deficient cells showed more aggressive leukemias compared to wild-type (69).…”
Section: Transcriptional Regulation and Transformation By H/mmentioning
confidence: 99%
“…Meis1 cooperates with HoxA9 in leukemogenesis, as its overexpression accelerates the emergence of HoxA9 -induced acute myeloid leukemia [ 37 ], whereas Prep1 overexpression does not accelerate HoxA9 -induced leukemia but rather delays its onset [ 38 ]. Acceleration of Meis-HoxA9 -induced leukemia on a Prep1 -hypomorphic background has also been reported [ 39 ]. Therefore, in order to interpret the hematopoietic phenotype of our Prep1-CKO mice, the complex interactions of each of these three TALE family members must be taken into account, as their patterns of interaction affect gene activation and/or inhibition, as well as each other’s protein stability, all of which can lead to different biological outcomes.…”
Section: Discussionmentioning
confidence: 99%